Estimation of Self-Medication and Associated Factors among Urban General Population in Part of Saurashtra Region of Gujarat, India - Nikita Savani; Trusha Kansagara; Meet Chauhan; Yamini Gurjar (Journal of Health Promotion and Behavior, 2023)
Background: Self-medication is a universal phenomenon and is practiced globally with varied frequency. In several studies, it has been found that the potential disadvantage of self-medication is a waste of resources, increased resistance to pathogens, and causes serious health hazards such as adverse reactions and prolonged suffering. This study aimed to estimate the practice and factors associated with self-medication among the urban general population. Subjects and Method: This community based cross-sectional study was conducted among general population of Amreli city, Gujarat, India from February to November 2022. A total of 110 subjects were include in this study. The dependent variable is self-medication practice. The independent variables are education, occupation, economic class. Data were collected by face-to-face interview using a semi-structured questionnaire with a recall period of 6 months’ experiences in 110 houses. Statistical analysis was done using Jamovi software. Results: Upper socio-economic class (OR= 1.74; 95% CI= 1.05 to 2.90; p= 0.031), highly educated (OR= 0.58; 95% CI= 0.41 to 0.83; p= 0.003) more likely to do self-medication than the lower socio-economic class and low education. Conclusion: Upper socio-economic and high education improve self-medication. Keywords: Self-medication, urban, reasons, adverse effects. Correspondence: Yamini J. Gurjar. Department of Community Medicine, Shantabaa Medical College & General hospital, Amreli, Suarashtra University, Gujarat, India-365601. Email: yjgurjar@gmail.com. Mobile: 9428625208